Declines and Resilience of Communities of Leaf Chewing Insects on Missouri Oaks Following Spring Frost and Summer Drought - Marquis, Robert J.; Lill, John T.; Forkner, Rebecca E.; Le Corff, Josiane; Landosky, John M.; Whitfield, James B. (Frontiers in Ecology and Evolution, 2019)
Extreme weather events dramatically impact populations of individual insect species but the consequences of such events for entire insect communities are not well documented. We present evidence that late spring frosts and summer drought negatively affect the community of insects found on Missouri oaks (Quercus alba and Q. velutina), amounting to a 23-186 fold decrease depending on the oak species, insect size and feeding guild, and the specific weather event. Spring faunas required three years or more following spring frosts to reach pre-event levels, whereas summer faunas were more resilient, rebounding within 1-2 years. The impact of summer drought on leaf tying caterpillars, however, lasted longer than that of the spring frost; it was five years before numbers of leaf ties reached pre-drought levels. Smaller species of leaf tying Lepidoptera took longer to recover than larger species following the drought. Overall, we found no evidence for a general decline in abundance, even a modest one, during the 20 years of study of faunas on oak trees in southeastern Missouri. However, the effects of drought reported here are likely to increase with time as the climate in the Midwest U.S. is only expected to become warmer and drier during the summer months. Similarly, the risk of late season frost damage to trees is expected to increase with predicted earlier onset of spring. Understanding the impact of such weather events on insect communities influences our ability to predict how habitat and landscape management, or lack thereof, will influence future patterns of insect abundance and diversity.